Strategies for Increasing Traditional Retail Stall Loyalty To Suppliers in The Era of Digital Transformation - Mujianto; Hartoyo; Nurmalina, Rita; Yusuf, Eva Z (School of Business, IPB University (SB-IPB), 2022)
The concept of marketing aims to build, maintain, and enhance mutually beneficial relationships between suppliers and partners. Therefore, this research recommends priority strategies for increasing traditional retail stall loyalty to suppliers in the new digital transformation era. This research was conducted in Indonesia's fast-moving consumer goods (FMCG) retail industry with data collected through a Forum Group Discussion (FGD) and in-depth interviews with several experts. These include top management of retail industry supply companies, principal of FMCG, General Chairperson of the Indonesian Retail Entrepreneurs Association, Secretary-General of the Indonesian Retail Entrepreneurs Association, Chair of the Chamber of Commerce and Industry, and academics who are also practitioners in the retail industry. The data collected were analyzed using the Analytical Hierarchy Process (AHP) approach. The results showed that merchandising and employees are the most dominant factors in forming retail stall loyalty to suppliers in the new digital transformation era. The company's main goal to increase retail stall loyalty to suppliers is by raising sales growth with the continuous rise in profits for supplier companies. Furthermore, the most important alternative strategy to increase retail stall loyalty to suppliers is product assortment and stock availability as the main alternative strategy. In conclusion, this research is useful for supply companies to establish relationships with traditional retail stalls in Indonesia. Keywords: analytical hierarchy process, merchandising, retail industry supplier strategy, retail service quality, website quality